2017
DOI: 10.1186/s40545-017-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Substance Agreements for Opioids in a Primary Care Practice

Abstract: BackgroundOpioids are widely prescribed for chronic non cancer pain (CNCP). Controlled substance agreements (CSAs) are intended to increase adherence and mitigate risk with opioid prescribing. We evaluated the demographic characteristics of and opioid dosing for patients with CNCP enrolled in CSAs in a primary care practice.MethodsWe conducted a retrospective cohort study of 1066 patients enrolled in CSAs between May 9, 2013 and August 15, 2016 for CNCP in a Midwest primary care practice.ResultsPatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Although the use and misuse of prescription opioids and opioid-related mortality in European countries are rather low, the number of opioid prescriptions has increased over the last decade (25). Despite recommendations and guidelines to avoid doses above 90 MME, a significant proportion of chronic noncancer pain patients still receive doses ≥90 MME (20,26,27). Additionally, questions are raised about the long term effects from other (nonaddictive) painkillers stronger than paracetamol and/or NSAIDs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use and misuse of prescription opioids and opioid-related mortality in European countries are rather low, the number of opioid prescriptions has increased over the last decade (25). Despite recommendations and guidelines to avoid doses above 90 MME, a significant proportion of chronic noncancer pain patients still receive doses ≥90 MME (20,26,27). Additionally, questions are raised about the long term effects from other (nonaddictive) painkillers stronger than paracetamol and/or NSAIDs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this epidemic, many researchers only focus on opioids instead of taking neuropathic pain medication, muscle relaxants, and other categories into account. Moreover, for chronic noncancer pain, recommendations and guidelines strive towards avoiding doses above 90 MME [ 26 , 27 , 28 ], wherefore a clinically important change in MME might be very relevant for clinicians that mainly aim to focus on opioid reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Despite clear guidance on maximum doses of opioids and the rationale for high-dose opioids becoming weaker, patients continue to rely on doses > 90 MME for pain management. A recent retrospective analysis of 1,066 primary health care records of patients prescribed opioids for chronic non-cancer pain, 9.7% were receiving ≥90 MME 59 . In 2012, the CDC reported that 10% of patients on prescription opioids were receiving a high-dose (>100 MME) from one doctor, and of those who overdosed, 40% were also prescribed their pain relief from a single doctor 29 .…”
Section: Discussionmentioning
confidence: 99%